Patterns of Discussion of Current Events by Internet Users: Case Study of Runet Sites - Natalya D. Pavlova; Victoriya A. Afinogenova; Taisiya A. Grebenschikova; Irina A. Zachesova; Tina A. Kubrak (Peoples' Friendship University of Russia (RUDN University), 2020)
The article deals with the problem of network discussions representing the new social reality of modern digital society. Communicative online activity sets an idea of what is happening, stimulating interest in the study of post-event Internet discourse. It is noted that the dominant role in this communication environment is played by the focus on promoting ones own world view and suppressing the activity of other users. This work continues a series of studies aimed at concretising these ideas. In previous studies conducted using the method of intent analysis, it was found that, in the process of discussion, there is a modification of referential objects and a shift in the intentional composition of discourse relative to the initial presentation of the event. In addition to it, differences in the types of post-event discourse were found in terms of the degree of conflict, the composition of intentions, etc. Verification of the revealed patterns associated with the intentional space of post-event discourse was the goal of the study carried out on the material of the discussion of the same event at different sites, i.e. the refusal of Prince Harry and Meghan Markle from the status of members of the royal family. According to the data obtained, a significant modification is confirmed during the discussion of referential objects and the intentional content of discourse regarding the received message: additional reference objects appear, their meaning is blurred, the number of categories of intentions increases many times with the increase of numerous emotionally coloured intentions. At the same time, a shift towards intentions of distancing and discrediting is revealed in relation to most of the discussed thematic objects. The discussion develops mainly due to the focus of users on the comments of interlocutors and the corresponding interactive objects, which is associated with the high dialogueness of post-event discourse. The data obtained allow us to advance in studying the discussion of events by Internet users and understanding which characteristics of the post-event Internet discourse are stable, and which are modified in connection with the leading function, theme, etc.